Effective Models of Reintegration for De-occupied Territories - Nina Rzhevska (Language, Culture, Politics)
The article aims to reveal the essence of the reintegration process of the occupied and de-occupied territories, determining the current state and characterizing the conflict in the East of Ukraine. Its components and implementation tools are analyzed, and foreign models of reintegration of the occupied and de-occupied territories are presented and evaluated; there is also determined the degree of their conformity for Ukraine. In this research, there was made an attempt to find the most effective model for the reintegration of Donbas, which would not only contribute to the demilitarization and restoration of state control in these territories, but also prevent the emergence of separatist movements, stimulate the process of returning, and integration of citizens to the social, cultural, economic and political life of their country of origin. It was stressed that the Ukrainian model for restoring the territorial integrity and reintegration of Donbas should be based on compromise and key issues that have a positive international grounding for which the government has a public support, combined with a strong national, international, and military one. There is a greater chance for working out a mutual standpoint of Ukraine and its international partners which would allow the conflict with Russia to be solved. It is noted that the problem remains since there is no consensus among citizens on the optimal way of restoring the territorial integrity of Ukraine. That is why there is an urgent need to create a comprehensive strategy to restore the territorial integrity and reintegration of Donbas. It will have a necessary impact on all the parties of the conflict, and result in a publicly supported compromise. This can be achieved despite the current domestic and international peculiarities of the process; help can be expected from international experience in restoring peace as well as from the government’s approach to the process of reintegration and shaping up a unified state.